Estudio de factibilidad para la creación de un complejo turístico en puerto Quito, provincia de Pichincha. - Toapanta Sosa, Sonia Marlene (2010)
This thesis project, entitled "Feasibility study for building a resort in Puerto Quito Canton Province Pichincha" emerged as a need to build on existing agrienvironmental conditions in the sector such as rivers, flora, fauna and others to provide a different tourist attraction in the sector. Moreover, the sector is characterized by its biodiversity because it has a rain forest, where you can observe wild vegetation, wildlife which include hawks, doves, wild turkeys, cervicabra, owls, waterfalls and other manifestations of environment suitable for Ecotourism. The development of the implementation of the resort will be linked to several resources that will be analyzed in terms of market studies, Technical, Administrative and Financial. Among the proposed objectives for this research project were: As a general objective is the following: Conduct a feasibility study for building a resort in Puerto Quito, Pichincha Province. The specific objectives were: Conduct a market study to determine the supply and demand to be the resort. Establish a technical study to determine the size, location and project engineering. Conduct a study organizational, legal and administrative framework for the resort. Prepare the financial study to determine the investment and project financing, as well as the financial evaluation by the various financial indicators NPV, IRR, sensitivity analysis and cost benefit ratio. From the academic point of view, the market study could be established to implement a resort in the area of Puerto Quito, Pichincha province, for which there is consumer acceptance to purchase this service. From a technical standpoint, the installed capacity was determined for the three types of service that will provide the resort, which is 8.030 for hosting service, to service the restaurant is finally 43.800 to service the pools scored 40.880 users annually, because the project is in its initial period will be used 90% of installed capacity, which corresponds to 7.227 users for the hosting service, while in the service of the restaurant is 39.420 and for service pools was 36.792, the above percentage will increase over the life of the project. In the management study defined the kind of resort which is considered a star cabins, "third category was also established that it has developed charts in the various hierarchical levels and functions of each of them also was elaborated an operational manual for the staff and the whole constitution and permits will be held. From the social point of view, the road project will allow recruitment of the same settlement area of the resort, and in doing so create jobs for families in the sector and thereby boost the local economy. From the economic point of view, describes the project's costs by giving us an investment of USD 118,189.79. It will be financed by a loan of 40,000.00 at 12% and the difference of capital will cover the project partners, the service will cost paid 12.01 USD for housing, restaurant for 2.20 USD and 2.36 pools USD in the first year of life of the project. Financial developments in the state was analyzed income where it was determined that net income for the first year is USD 113,798.14 finally determined the effect that the resort has to cover its operations through cash flow. Finally, in the criteria for evaluating the project, study the net present value, internal rate of return, sensitivity analysis, cost benefit and payback period of capital. The net present value of 488,267.21, the same as that which resulted positive for the project is considered feasible. The internal rate of return is 81.05%, this was greater than the rate of interest that overrides the financial identities. In the sensitivity analysis of costs increased 6.70% and a decrease in revenues of 4.20%, which indicates that the project is not sensible. With reference to the cost benefit ratio is 7.69 which means that for every dollar invested the project will have a profit of $ 6.69 cents for all three services, the project investment will recover in a year, one month and 14 days. For diagnosis, it was necessary to apply techniques such as bibliography, direct observation, surveys with the families of the province of Pichincha in their respective counties and part of the province of Santo Domingo de los Tsáchilas. For information processing methods were used for analysis, synthesis and description. Final product was obtained as the current situation of tourism in Canton Puerto Quito, Pichincha Province and the Province of Santo Domingo de los Tsáchilas. We conclude that Puerto Quito for quality in natural and cultural attractions, can have a tourism product.